The Challenges of Remote E-Assessments During Covid-19 Outbreaks Among Undergraduate Engineering Programs - Asnul Dahar Minghat; Noor Azihah Abdullah; S. Suparman (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to identify the challenges faced by undergraduate students with remote e-assessments during Covid-19 outbreaks. The study was guided by the following specific objectives: to identify the level of students’ challenges to remote e-assessments in four major areas which are internet connectivity, academic integrity, disturbance in-home learning, and overflow of assignments, to identify significant differences between student’s location and family income category with four major areas of challenges to remote e-assessments. To achieve the objectives, students from one of the undergraduate programs at University Teknologi Malaysia have been chosen as the sample size. This study was designed to follow a single approach which is quantitative methods by means questionnaire surveys were distributed among the students and the data gathered was analyzed using SPSS software. The results from the analysis indicated that students facing the highest level of challenges to remote e-assessments during Covid-19 outbreaks are the overflow of assignments. The result from the study also showed that there is a significant difference between students’ family income and four major challenges to remote e-assessments. The recommendations are that organizations, especially at the university level should try to give great emphasis on e-assessments activities to develop those smooth practices to a great extent since the practice may eventually replace the traditional examination.